Nanoparticles of cerium dioxide – an effective antiviral agent and adjuvant of biologically active molecules - Shydlovska, Olga; Kharchenko, Eugene; Osenniy, Ivan; Spivak, Mykola; Shcherbakov, Alexander; Zholobak, Nadiya (ScienceRise: Biological Science, 2018)
There was studied the influence of cerium dioxide nanoparticles on the cytokines production in the conditions of their application in the composition with interferon and as an independent drug. Applying the CDN in combination with IFN showed an increased interferon response of experimental mice compared with unmodified IFN. IFN-CDN nanobiocomplex does not increase the level of TNF production, which indirectly indicates the safety of the applying of such complex. There was studied the effect of CDN as a therapeutic agent on the cytokines production in the treatment of modeled herpes simplex virus-1 infection. It was found that CDN is able to increase IFN and TNF levels and prolong their effects. It was found that NDC is able to increase the level of IFN and FNP and prolong their effects. The application of CDN caused increasing of TNF levels and their prolonging action. There was shown the significant increasing (to three weeks) in IFN titers on the step of decreasing in TNF titers in the group, that was infected and then treated with NCD. In the non-treated group and in the aciclovir-treated animal group, IFN titers were significantly lower.The obtained results testify to the effectiveness of NDC as a modifying agent for interferon and as a promising agent for the treatment of systemic herpetic infection